Do Cyberbullying Victims Feel more Entitled to Bully Others Online? The Moderating Role of Gender - Ding, Huimin; Zhao, Chengjia; Huang, Feng; Wei, Hua; Lei, Li (Journal of interpersonal violence, 2025)
Previous studies have found that adolescent cyberbullying victimization is associated with cyberbullying perpetration and have explored the potential mediating mechanisms between the two. Although some valuable research has been accumulated, further exploration is needed on the underlying mechanisms of why cyber victims are transformed into cyberbullying perpetrators. Based on the General Aggression Model of Cyberbullying and the Social Role Theory, this study examined the mediating role of psychological entitlement and the moderating role of gender on the relationship between cyberbullying victimization and cyberbullying perpetration. A questionnaire survey was conducted on 836 adolescents, utilizing the cyberbullying victimization scale, cyberbullying perpetration scale, and psychological entitlement questionnaire. The results found that (a) cyberbullying victimization, psychological entitlement, and cyberbullying perpetration were significantly and positively correlated with each other; (b) after controlling for gender and age, cyberbullying victimization significantly and positively predicted cyberbullying perpetration and psychological entitlement mediated the relationship between cyberbullying victimization and cyberbullying perpetration; (c) Gender moderates the relationship between cyberbullying victimization and cyberbullying perpetration. Specifically, compared with the girls, cyberbullying victimization had a greater effect on cyberbullying perpetration among boys. The results of this study suggest that cyberbullying victims consider that they have more entitlement to bully others online. These findings support the General Aggression Model of Cyberbullying and provide new insights for the prevention and intervention of cyberbullying perpetration.